Effervescence religieuse et gouvernance: L'exemple des Assemblées de Dieu du Burkina Faso - Laurent, Pierre Joseph (La politique africaine, 2002)
The success of the Assemblies of God in Burkina Faso must be situated in the context of an "insecure modernity", in which longstanding links between solidarity and consensus disintegrate and an ineffective state does not assure security for a large part of the population. By offering distinct spaces of sociability, and by coupling conversation with rituals for divine healing, the Assemblies of God have emerged as a miraculous solution to solitude, illness, adversity, physical and social suffering, and the quest for selfhood. (Polit afr/DÜI)